Bounds for Toader Mean in Terms of Arithmetic and Second Seiffert Means - He, Zai-Yin; Jiang, Yue-Ping; Chu, Yu-Ming (Communications in Mathematics and Applications, 2019)
In the article, we prove that the double inequalities\begin{align*}&α_{1}T(a,b)+(1-α_{1})A(a,b)
Keywords: Toader mean; Second Seiffert mean; Arithmetic mean